PENGARUH EKSTRAK DAUN KARAMUNTING (Rhodomyrtus tomentosa) TERHADAP JUMLAH SEL NAUTROFIL PADA PULPA - Reisa Dahliani; Muhammad Yanuar Ichrom Nahzi; Raden Harry Dharmawan Setyawardhana (Dentin, 2021)
ABSTRACTBackground: Caramunting leaf (Rhodomyrtus tomentosa) is an alternative pulp capping material that can provide anti-inflammatory effects. Phytochemical screening showed that caramunting leaf has secondary metabolites that inhibit oxidant production by neutrophils, monocytes, and macrophages. The decrease in inflammatory activity was marked by a decrease in the number of neutrophils on 3rd day as the inflammatory process decreased. Purpose: To determine and analyze the effect of Karamunting leaf extract (Rhodomyrtus tomentosa) at the dose of 800mg/KgBB on the neutrophil number in pulp inflammation of Wistar rats on 1st and 3rd day. Methods: This study was true experimental research (post-test only with control group design) using 30 Wistar rats divided into 6 groups which were given pulp capping material on the 1st and 3rd day using calcium hydroxide, Karamunting leaf extract, and without pulp capping material. The number of neutrophils was observed microscopically on the 1st and 3rd day. Results: One-way ANOVA and Post hoc Bonferroni test showed significant differences (p<0.05) in all groups. Conclusion: The administration of Karamunting leaf extract (Rhodomyrtus tomentosa) at the dose of 800mg/KgBB had a significant effect on reducing the neutrophil number in pulp inflammation of Wistar rats on 1st and 3rd day. Keywords: Karamunting leaf (Rhodomyrtus tomentosa), neutrophils, pulp capping. ABSTRAKLatar Belakang: Daun Karamunting (Rhodomyrtus tomentosa) merupakan salah satu bahan alternatif pulp capping yang dapat memberikan efek antiinflamasi. Skrining fitokimia menunjukan daun karamunting memiliki metabolit sekunder yang menghambat produksi oksidan oleh neutrofil, monosit dan makrofag. Penurunan aktivitas inflamasi salah satunya ditandai oleh penurunan jumlah neutrofil dihari ke-3 seiring berkurangnya proses inflamasi. Tujuan: Mengetahui dan menganalisis pengaruh pemberian ekstrak daun karamunting (Rhodomyrtus tomentosa) dosis 800mg/KgBB terhadap jumlah sel neutrofil pada inflamasi pulpa tikus wistar di hari ke-1 dan ke-3. Metode: Penelitian ini merupakan penelitian eksperimental murni dengan rancangan post-test only with control group design menggunakan 30 ekor tikus wistar dibagi menjadi 6 kelompok yang akan diberikan bahan pulp capping pada hari ke-1 dan ke-3 menggunakan kalsium hidroksida, ekstrak daun karamunting, dan tanpa pemberian bahan pulp capping. Jumlah neutrofil diamati secara mikroskopis di hari ke-1 dan hari ke-3. Hasil: One-way Anova dan Post hoc bonferroni menunjukkan perbedaan bermakna (p<0,05) pada semua kelompok. Kesimpulan: Pemberian ekstrak daun karamunting (Rhodomyrtus tomentosa) dosis 800mg/KgBB memberikan pengaruh yang signifikan terhadap penurunan jumlah sel neutrofil pada inflamasi pulpa tikus wistar di hari ke-1 dan ke-3. Kata kunci : daun karamunting (Rhodomyrtus tomentosa), neutrophil, pulp capping.